NIMG-34. MULTI-PARAMETRIC MR-PET IMAGING PREDICTS PHARMACOKINETICS AND CLINICAL RESPONSE TO GDC-0084 IN HUMAN RECURRENT HIGH-GRADE GLIOMA. (11th November 2019) - Ellingson, Benjamin; Yao, Jingwen; Raymond, Catalina; Nathanson, David; Simpson, Jeremy; Garner, James; Olivero, Alan; Mueller, Lars; Rodon, Jordi; Gerstner, Elizabeth; Cloughesy, Timothy; Wen, Patrick
Abstract: Alterations in the PI3K pathway are found in the majority of malignant gliomas, but lack of efficacy has caused investigators to question the viability of this target, particularly due to lack of brain penetration. GDC-0084 was specifically optimized to penetrate the brain, targeting both PI3K and mTOR. Since these two targets alter tumor vascularity and metabolism, respectively, we hypothesized that multi-parametric MR-PET could be used to quantify the response, estimate pharmacokinetic (PK) parameters, and predict progression-free survival (PFS) in patients with recurrent malignant gliomas. In this first-in-man, multicenter, phase I, dose-escalation study (NCT01547546), we show in 47 patients that the measured maximum concentration (Cmax) of GDC0084 was associated with a decrease in enhancing tumor volume (P=0.0287) and an increase in fractional anisotropy (FA) (P=0.0418). Post-treatment tumor volume, 18F-FDG uptake, Ktrans, and relative cerebral blood volume (rCBV) were all correlated with Cmax. A linear combination of change in 18F-FDG PET uptake, apparent diffusion coefficient (ADC), FA, Ktrans, vp, and rCBV were able to estimate both Cmax (R2=0.4113, P< 0.0001) and drug exposure (AUC) (R2=0.3481, P< 0.0001). Using this composite multi-parametric MR-PET imaging response biomarker to predict PK, patients with an estimated Cmax >0.1 uM and AUC > 1.25 uM*hr demonstrated significantly longer PFS compared with patients with a lower estimated concentration and exposure (P=0.0039 and P=0.0296, respectively). Results from the current study suggest composite biomarkers created from multi-parametric MR-PET imaging targeting metabolic and/or physiologic processes specific to the drug mechanism of action may be useful for subsequent evaluation of treatment efficacy for larger phase II-III studies.